2005
DOI: 10.1111/j.1582-4934.2005.tb00384.x
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive view of polyamine and histamine metabolism to the light of new technologies

Abstract: Polyamines and histamine are biogenic amines with multiple biological roles. In spite of the evidence for the involvement of both polyamines and histamine metabolism impairment in several highly prevalent pathological conditions multiple questions concerning the molecular processes behind these effects remain to be elucidated. More comprehensive and systemic studies intergrating molecular biology, biophysical and bioinformatics tools could contribute to accelerate the advances in this research area. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 82 publications
0
17
0
1
Order By: Relevance
“…They have pleiotropic effects, with a recognized major role as metabolic regulators of the rate and fidelity of macromolecular synthesis, cell proliferation/death balance, and cell differentiation, among others (11)(12)(13)(14)(15). Direct interactions between polyamines and nucleic acids (16,17), proteins (18 -21), and biological membranes (22) have been proposed to explain some of these biological functions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They have pleiotropic effects, with a recognized major role as metabolic regulators of the rate and fidelity of macromolecular synthesis, cell proliferation/death balance, and cell differentiation, among others (11)(12)(13)(14)(15). Direct interactions between polyamines and nucleic acids (16,17), proteins (18 -21), and biological membranes (22) have been proposed to explain some of these biological functions.…”
mentioning
confidence: 99%
“…However, most of this information is very disperse and not integrated in a comprehensive, systemic framework. On the other hand, many therapeutic strategies based on the specific inhibition of one of the key enzymes of polyamine metabolism have failed, mostly due to the presence of compensating mechanisms in polyamine metabolism that contribute to the buffering of those effects elicited when only an enzyme is the target (15,40). The structure of the reaction diagram of polyamine metabolism in mammals is relatively complex, consisting of a bi-cycle having two required entrances (ornithine and S-adenosylmethionine) and several alternative exits (Fig.…”
mentioning
confidence: 99%
“…The reduction in cellassociated histamine 72 -96 hours post activation was not due to histamine release from the cell during this time frame. One possibility for the decrease is that the cell-associated histamine in BMMC is metabolized by the same cytoplasmic enzymes that metabolize histamine in tissues, histamine-N-methyl transferase (HMT) and diamine oxidase (DAO) [23,24]. Mast cells and basophils are the only cell types that store histamine; however, other cell types can be induced to produce histamine.…”
Section: Discussionmentioning
confidence: 98%
“…Holistic approaches to the study of the polyamine/histamine metabolic interplay in cancer and chronic inflammation As stated in this review, a relationship between the metabolisms of polyamine and histamine has been deduced from multiple studies, and this relationship is very likely to play a role in inflammation and cancer [45,60], though this process is still poorly understood. The metabolic pathways are part of a very intricate network that is sensitive to cell and tissue specificity, the microenvironment and many other factors that make every particular condition unique, and contradictory data have been reported.…”
Section: Mast Cells: An Important Link Between the Polyamine/histaminmentioning
confidence: 99%
“…In addition, compounds such as quercetin, which has anti-inflammatory and cancer-prevention properties, are able to inhibit mast cell secretion and downregulate HDC expression (reviewed in [58]). Finally, Soucek et al [59 ] have shown that activation of Myc, a pleiotropic transcription factor overexpressed in many cancers, triggers recruitment of mast cells to the tumor microenvironment; this recruitment is required for tumor expansion, as the administration of mast cell inhibitors rapidly provoke hypoxia and tumor cell death.Holistic approaches to the study of the polyamine/histamine metabolic interplay in cancer and chronic inflammation As stated in this review, a relationship between the metabolisms of polyamine and histamine has been deduced from multiple studies, and this relationship is very likely to play a role in inflammation and cancer [45,60], though this process is still poorly understood. The metabolic pathways are part of a very intricate network that is sensitive to cell and tissue specificity, the microenvironment and many other factors that make every particular condition unique, and contradictory data have been reported.…”
mentioning
confidence: 99%